3分之3x-2-2分之5x+1≥3分之9-2x
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 09:53:43
3分之3x-2-2分之5x+1≥3分之9-2x3分之3x-2-2分之5x+1≥3分之9-2x3分之3x-2-2分之5x+1≥3分之9-2x两边乘以6得2(3x-2)-3(5x+1)>=2(9-2x)6
3分之3x-2-2分之5x+1≥3分之9-2x
3分之3x-2-2分之5x+1≥3分之9-2x
3分之3x-2-2分之5x+1≥3分之9-2x
两边乘以6得
2(3x-2)-3(5x+1)>=2(9-2x)
6x-4-15x-3>=18-4x
-5x>=25
x
3分之3x-2-2分之5x+1≥3分之9-2x
x-2-x分之3 分之 1+x分之6 +x^2分之5
解不等式组 5分之3x-7<2分之x-2 4分之x-12分之2x-1≥6分之1-3分之x
x:7分之4=3分之1 8分之15:x=2分之3 6分之1÷10分之9=5分之2:x
3分之2:3分之1=9分之x
6分之1x(9分之6+3分之2)
2分之1x(6分之5-3分之2)
【(5分之2根号25X)-(3X根号X分之1)+(2分之9根号9分之X³)】
7分之4÷X=8分之5X-4分之3X=5分之45分之3X÷3分之2=9分之84分之1-2X=6分之1
3分之3x-2-3分之9-2x≤2分之5x+1
(x²-9分之5)+(x+3分之2x)=-5分之1
x的平方-9分之2x+3-x分之1+x+3分之x+2
方程3分之+4分之3x=12分之5x-5分之3=15分之87分之4x÷7分之6=2分之3脱式计算5分之4-6分之5×10分之34分之3÷8分之5×32分之1512分之11+3分之1÷9分之5+5分之2(3分之2-2分之1)÷(3分之5×6分之5)5分之9+(
分式方程、会滴来、1.2x-3分之x+3-2x分之5=22.x+1分之x=3(x+1)分之2x+13.x分之9=x-1分之84.x-1分之2x+x+2分之2=25.1-x分之3-2x-1=x-3分之x+2
分式方程、会滴来哦1.2x-3分之x+3-2x分之5=22.x+1分之x=3(x+1)分之2x+13.x分之9=x-1分之84.x-1分之2x+x+2分之2=25.1-x分之3-2x-1=x-3分之x+2
1-4分之6x-7≥3分之2x+5-2分之2分之2x-1
x+1分之1-x+2分之1-x+3分之1+x+4分之1
15分之2X÷9=5分之4 12分之5+X=3 3分之1X×9分之4=6分之1